Senyawa Bioaktif dari Tanaman sebagai Kandidat Terapi Gangguan Spektrum Autisme - Wenas, Desy Muliana (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2025)
Indonesia has the second largest natural resources in the world. This literature study is intended to summarize the use of herbal and traditional medicines in the treatment of autism in additional therapy. Medicinal plants that are effective for autism show strong antioxidant activity combined with anti-inflammatory activity and effects on neurotransmitters. The study was conducted using a literature study method using the Pubmed, Google Scholar, and Science Direct databases and using different combinations of keywords autism, ASD, herbal, traditional plant, neutrotransmitter. The results of a review of several articles indicate that pegagan, ginko biloba, and ginseng plants have potential as candidate therapies for ASD patients. Plants as traditional medicine and important sources of modern pharmaceutical compounds have great potential in supporting well-being and managing complex symptoms in people with autism.